Educação alimentar e nutricional como força motriz do desenvolvimento da interdisciplinaridade - Araújo, Alessandra Teixeira Miranda (2015)
Nutrition food education (EAN) is an important role in the growing of children as it is when there is the formation of habits, character and personality. The school can and should contribute to the acquisition of healthy habits, exercising direct influence, expanding or even modifying practices derived from the family environment. The objective of this research was to analyze the growing and application of interdisciplinarity in special educational activities (project "Amiguinhos da Saúde"), related to the EAN and performed by teachers of early childhood education and primary education in private schools in São Paulo. The quantitative and qualitative research used various tools and techniques: logbook (to record the most important events throughout the monitoring process), satisfaction survey (to check the reaction of teachers through training workshops), focus groups (which generated data for evaluation of the application of EAN as a strategy for achieving interdisciplinarity, submitted for examination by the CSD), beyond words clouds ("wordle)" and documentary research of teachers class daily. This study was in its first phase (training) with the collaboration of 14 coordinators, 11 masterminds and 126 teachers. This set of three coordinators, three masterminds teachers and 14 made up the group submitted to evaluation of the application in the second phase of the research. The "Amiguinhos da Saúde" proved to be decisive for the implementation of initiatives that involved the EAN. Different activities and applications permeated various disciplines of the curriculum in an interdisciplinary way. Results show review that there was a positive demonstration of individual and collective reflections and reactions in the application of concepts learned on EAN. Developed educational strategies have shown that the actions in the classroom expanded by various disciplines and extrapolated the school, expressing the possibilities of interdisciplinarity practiced in kindergarten and elementary school